The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1016/j.ajhg.2018.07.006
|View full text |Cite|
|
Sign up to set email alerts
|

IRF2BPL Is Associated with Neurological Phenotypes

Abstract: Interferon regulatory factor 2 binding protein-like (IRF2BPL) encodes a member of the IRF2BP family of transcriptional regulators. Currently the biological function of this gene is obscure, and the gene has not been associated with a Mendelian disease. Here we describe seven individuals who carry damaging heterozygous variants in IRF2BPL and are affected with neurological symptoms. Five individuals who carry IRF2BPL nonsense variants resulting in a premature stop codon display severe neurodevelopmental regress… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
81
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(98 citation statements)
references
References 77 publications
(111 reference statements)
3
81
0
Order By: Relevance
“…The affected members of these families displayed typical self-limited DP with late onset of puberty but full adult development by the age of 18 years. None of the affected individuals had neurological or other associated phenotypic abnormalities (23). Complementing previous studies in rats and non-human primates (7), we have shown that Eap1 is also abundantly expressed in the peri-pubertal mouse hypothalamus.…”
Section: Discussionsupporting
confidence: 86%
“…The affected members of these families displayed typical self-limited DP with late onset of puberty but full adult development by the age of 18 years. None of the affected individuals had neurological or other associated phenotypic abnormalities (23). Complementing previous studies in rats and non-human primates (7), we have shown that Eap1 is also abundantly expressed in the peri-pubertal mouse hypothalamus.…”
Section: Discussionsupporting
confidence: 86%
“…It is an intronless gene, formerly known as c 14orf4 . It encodes the interferon regulatory Factor 2‐binding protein‐like protein, a zinc finger/RING finger protein that functions as a transcriptional modulator (Macrogliese et al, ). In addition to transcriptional modulation, IRF2BPL functions as a E3 ubiquitin ligase that targets B‐catenin for proteasome degradation in gastric cancer (Higashimori et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to transcriptional modulation, IRF2BPL functions as a E3 ubiquitin ligase that targets B‐catenin for proteasome degradation in gastric cancer (Higashimori et al, ). Studies of the orthologous gene, pits , in drosophila have demonstrated its importance in the nervous system and shown that truncated proteins are not hypermorphic or neomorphic and the disease mechanism likely involves loss of function (Macrogliese et al, ). The first clinical descriptions of individuals with IRF2BPL variants were published in 2018.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with a recent study that used imprecise P-element excision to generate three pits alleles, two of which were homozygous viable, whilst the third was semi-lethal (LIAW 2016). An independent study used recombination mediated cassette exchange to generate pits mutant alleles, which were hemizygous lethal (MARCOGLIESE et al 2018). We utilised our pits mutant alleles to further test whether Tgi requires pits to retard eye growth.…”
Section: Tgi Requires Pits To Suppress Eye Growthmentioning
confidence: 99%